Dampak Implementasi XBRL terhadap Risiko Informasi - Pamungkas, Yuna Adhi; Kristanto, Ari Budi (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
This study aims to determine the impact of the implementation of XBRL on information risk for corporate financial reporting. The population in this study were all manufacturing companies listed on the IDX from 2012 to 2017. The samples in this study were obtained by purposive sampling method with the criteria (1) Manufacturing companies listed on the IDX in 2012 to 2017 (2) Having complete research data. The sample used in this study amounted to 84 companies registered in IDX in 2012 to 2017. Data analysis technique used multiple regression analysis to see the effect of XBRL implementation on information risk with company size and leverage as control variables. The results of this study indicate that the implementation of XBRL has a significant negative effect on information risk; Firm size and corporate action have a significant positive effect on information risk and leverage has a significant negative effect on information risk.Â Financial reports that use XBRL will reduce information risk so it can help stakeholders to make a good quality business decisions. <!–[if supportFields]><![endif]–>